2004
DOI: 10.1523/jneurosci.4442-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceptual Learning on Neuronal Responses in Monkey Visual Area V4

Abstract: Previous studies have shown that perceptual learning can substantially alter the response properties of neurons in the primary somatosensory and auditory cortices. Although psychophysical studies suggest that perceptual learning induces similar changes in primary visual cortex (V1), studies that have measured the response properties of individual neurons have failed to find effects of the size described for the other sensory systems. We have examined the effect of learning on neuronal response properties in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
334
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(384 citation statements)
references
References 47 publications
44
334
6
Order By: Relevance
“…Schoups et al (2001) found that training of an orientation discrimination causes an increase in the slope of the tuning curve of V1 neurons. In addition, Yang and Maunsell (2004) found that the average bandwidth of the orientation tuning curve becomes narrower for the trained population of neurons in V4, especially for neurons whose preferred orientation was close to the trained orientation, a finding confirmed by Raiguel et al (2006). Moreover, in the current study, subjects who showed larger behavioral improvement also showed a greater reduction of brain activations in visual cortex.…”
Section: Changes In Visual Cortex Activation During Perceptual Learningsupporting
confidence: 79%
See 2 more Smart Citations
“…Schoups et al (2001) found that training of an orientation discrimination causes an increase in the slope of the tuning curve of V1 neurons. In addition, Yang and Maunsell (2004) found that the average bandwidth of the orientation tuning curve becomes narrower for the trained population of neurons in V4, especially for neurons whose preferred orientation was close to the trained orientation, a finding confirmed by Raiguel et al (2006). Moreover, in the current study, subjects who showed larger behavioral improvement also showed a greater reduction of brain activations in visual cortex.…”
Section: Changes In Visual Cortex Activation During Perceptual Learningsupporting
confidence: 79%
“…The results, when superimposed on retinotopic maps of individual subjects, revealed that the reduced activations were seen as early as V1 but mainly in V3-V4 and beyond, all of which contain populations of neurons that are sensitive to stimulus contrast (Boynton et al, 1999;Reynolds et al, 2000;Gardner et al, 2005;Lu and Roe, 2007). Previous studies reported perceptual learning effects in early visual areas, including V1 and V4, when subjects were trained on fine discriminations of simple visual features, such as orientation and texture (Schiltz et al, 1999;Schoups et al, 2001;Schwartz et al, 2002;Furmanski et al, 2004;Yang and Maunsell, 2004;Sigman et al, 2005;Raiguel et al, 2006), and in motion-sensitive areas MT and MST, when subjects were trained on motion discrimination tasks (Zohary et al, 1994;Vaina et al, 1998). These results, together with ours, suggest that learning occurs in visual areas in which the task-relevant visual information is processed.…”
Section: Changes In Visual Cortex Activation During Perceptual Learningmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast, it has been shown that learning does not alter the topography or basic receptive field properties (e.g., size, location, or orientation selectivity) in V1 (34,35). Furthermore, training-dependent changes on orientation tuning are shown to be more pronounced in V4 (36,37), whereas effects in V1 are shown to be task-dependent and may engage topdown facilitation mechanisms (35,(38)(39)(40). It is possible that the lack of significant learning effects in V1 in our study is caused by the large spacing between contour elements that may prevent integration within the small receptive fields of V1 neurons.…”
Section: Discussionmentioning
confidence: 93%
“…These powers of neuroplasticity stem from the mammalian brain's ability to reorganize in response to experience (1)(2)(3)(4). In sensory cortex, plasticity induced by sensory tasks optimizes the brain's capacity for future performance through amplifying activity that is most informative about reinforcement (4)(5)(6). Dominant models of this plasticity are activity-dependent (2,7,8), and associated learning is presumed to be a function of endogenous processes reliant on gene activation, because long-term plasticity and long-term memory require protein synthesis (9) following expression of immediate-early genes such as Arc (10,11).…”
mentioning
confidence: 99%